The development of German criminal law against corruption in the private sector - Dannecker, Gerhard (Organizational crime, 2023)
Public and private corruption is no longer a problem of developing and emerging countries alone but has developed into a cross-border phenomenon. The German legislator has reacted to this development by implementing the international guidelines and requirements of the European Union, the Council of Europe, the UN, and the OECD. It pursues the goal of taking legal measures against private and public corruption by means of penal and administrative sanctions and tax measures.
Gesehen am 11.05.2023